2018 IEEE International Conference on Soft Robotics (RoboSoft) 2018
DOI: 10.1109/robosoft.2018.8405387
|View full text |Cite
|
Sign up to set email alerts
|

Muscle textile to implement soft suit to shift balancing posture of the body

Abstract: This study reports on the design and construction of a body support suit based on two novel concepts: muscle textile and shifting the balancing posture of the body. The muscle textile is an active textile composed of soft thin muscles that provides a large supporting force, and is flexible and lightweight. Shifting the balancing posture of the body involves changing its neutral posture while relaxing the muscles, making it easier to perform tasks in uncomfortable positions and simplifying the control system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Development for shoulder SWRs became a more active research topic in the later 2010s as NASA began to invest in the "Armstrong," a wearable suit for astronauts that used tendons to assist the shoulder (Kadivar et al 2017). It was around the time of this development that increasingly advanced textile actuators emerged in the field (Natividad and Yeow 2016;O'Neill et al 2017) and McKibben muscles showed more sophisticated and effective designs (Abe et al 2018). The shoulder has proven to be a difficult joint to assist, and some of the most prevalent SWRs tackling this goal are still seeking to find actuators that most closely resemble human muscle functions and placements (Abe et al 2019).…”
Section: Shouldermentioning
confidence: 99%
See 1 more Smart Citation
“…Development for shoulder SWRs became a more active research topic in the later 2010s as NASA began to invest in the "Armstrong," a wearable suit for astronauts that used tendons to assist the shoulder (Kadivar et al 2017). It was around the time of this development that increasingly advanced textile actuators emerged in the field (Natividad and Yeow 2016;O'Neill et al 2017) and McKibben muscles showed more sophisticated and effective designs (Abe et al 2018). The shoulder has proven to be a difficult joint to assist, and some of the most prevalent SWRs tackling this goal are still seeking to find actuators that most closely resemble human muscle functions and placements (Abe et al 2019).…”
Section: Shouldermentioning
confidence: 99%
“…Fluidic actuation approaches specific to the elbow begun to emerge in the 2010s with other pneumatic SWRs and varied stylistically to match the specific need the exosuit is trying to fulfill (Abe et al 2018). Some used a bellows-type design to push the elbow into extension and pull it into flexion from the armpit area (Oguntosin et al 2015), while others designed for rotary actuators placed on the exterior side of the elbow joint to apply a rotational torque to induce flexion assistance (Aragane et al 2008;Noritsugu et al 2008;Thalman et al 2018).…”
Section: Elbowmentioning
confidence: 99%
“…3 Although pneumatic exoskeletons were initially made of mostly rigid components, 4,5 more recently they have been developed with more flexible, compliant elements. [6][7][8][9][10][11][12][13][14][15] Soft exoskeletons and artificial muscles have also used a range of power sources, including cable-tendon-driven mechanisms, that is, Exosuit, 16 Myosuit, 17 and XoSoft 18 ; direct electro-mechanical energy transduction in polymers, for example, polyvinyl chloride (PVC) gel, 19,20 dielectric elastomers, 21,22 dielectrophoretic liquid zipping actuators, 23 and Peano-HASEL 24 ; and thermomechanical actuation such as coiled polymer. 25 PAMs are soft, flexible contractile actuators that change shape and contract when activated by pressurized air.…”
Section: Introductionmentioning
confidence: 99%
“…Sogang University in Korea developed a exoskeleton namely SUBAR (Chen et al, 2013;Hwang and Jeon, 2018), which could estimate the muscular torque of its wearer. Singapore's Nanyang Technological University (Mertz, 2012) and Harvard University (Abe et al, 2018) have also made solid progress in the development of assisted exoskeletons. The Chinese University of Science and Technology designed an exoskeleton robot driven by a servo motor and developed a fuzzy algorithm for lower extremity exoskeleton (Huang et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%